Classification of EEG signals using MLP based on categorical and dimensional perceptions of emotions. - Yaacob, Hamwira Sakti; Abdul Rahman, Abdul Wahab; Kamaruddin, Norhaslinda (2013)
Emotions are frequently studied based on two approaches; categorical and dimensional. In this study, Multi- Layer Perceptron (MLP) was employed to classify four affective states as posited from these approaches. It was observed that emotional states viewed from the dimensional perspective are well discriminated using memory test. In addition to that, the dynamic for each of the four emotions were also presented, in which it was also indicated that an emotional state does not occur abruptly.